Synthesis and properties of self-assembled ultralong core-shell Si3N4/SiO2 nanowires by catalyst-free technique. Issue 16 (November 2019) - Chen, Yang; Zhang, Chang; Wang, Ning; Jensen, Martin; Li, Xianfeng; Zhang, Xingxiang
Abstract: Self-assembled ultralong Si3 N4 /SiO2 nanowires (SiNNWs) with core-shell structure are prepared by air jet-spinning followed by high-temperature calcination employing low-cost fumed nano silica and industrial polyacrylonitrile as raw materials. Without using metal catalysts or reductive atmosphere, Si3 N4 /SiO2 nanowires are generated through autocatalysis and self-assembly. The ultralong SiNNWs are uniform and continuous throughout the entire length with a 3–4 nm amorphous SiO2 shell layer on surface of the Si3 N4 . The diameter of the SiNNWs is about 80–200 nm with the length being at centimeter level and the main component of the SiNNWs is the standard hexagonal cell of α-Si3 N4 . Moreover, the photoluminescence spectrum of SiNNWs exhibits an intense blue-green light emission at room temperature. The self-assembly mechanism of the SiNNWs is discussed.